Emotional Intelligence and Leadership Trait among Master Teachers - Lucero, Leilani C; Ocampo, Jr., Jose M (MIMBAR PENDIDIKAN, 2019)
ABSTRACT: Many classroom teachers get promoted to a leadership role as in the case of Master Teachers in the Department of Education (DepEd) in the Philippines. This requires a shift in role or expansion of scope and nature of work as they adjust and accommodate the new assignment. Hence, this shift is worth studying to understand how they fare and what assistance can be given them to be effective in doing their tasks. This is the purpose of the current study focused on determining the emotional intelligence and leadership trait of the Master Teachers. Using a descriptive-correlational research method involving 45 respondents from the 10 Senior High Schools in Pasig City with Master Teachers, the study identified their emotional intelligence and leadership trait, and determined the significant correlations between the two as perceived by the participants. The results show that the respondents were highly emotionally intelligent in managing own emotions, managing othersâ€™ emotions, and utilization of emotions, but they got above average emotional intelligence in the perception of emotions. On the other hand, the measure of leadership trait showed that they had high leadership trait in all the five major leadership traits. KEY WORD: Emotional Intelligence; Leadership Trait; Master Teacher.Â ABSTRAKSI: â€œKecerdasan Emosional dan Sifat Kepemimpinan diantara Guru-guru Kepala Sekolahâ€. Banyak guru kelas dipromosikan ke peran kepemimpinan seperti dalam kasus Guru-guru Kepala Sekolah di Departemen Pendidikan (DepEd) di Filipina. Ini membutuhkan pergeseran peran atau perluasan ruang lingkup dan sifat pekerjaan saat mereka menyesuaikan dan mengakomodasi tugas baru. Oleh karena itu, perubahan ini layak dipelajari untuk memahami bagaimana taraf mereka dan bantuan apa yang dapat diberikan kepada mereka agar efektif dalam melakukan tugas-tugas mereka. Ini adalah tujuan dari penelitian ini yang berfokus pada menentukan kecerdasan emosi dan sifat kepemimpinan dari Guru-guru Kepala Sekolah. Menggunakan metode penelitian deskriptif-korelasional yang melibatkan 45 responden dari 10 SMA (Sekolah Menengah Atas) di Kota Pasig dengan Guru-guru Kepala Sekolah, penelitian ini mengidentifikasi kecerdasan emosional dan sifat kepemimpinan mereka, dan menentukan korelasi yang signifikan antara keduanya seperti yang dirasakan oleh para peserta. Hasil kajian menunjukan bahwa responden sangat cerdas secara emosional dalam mengelola emosi sendiri, mengelola emosi orang lain, dan memanfaatkan emosi, tetapi mereka mendapat kecerdasan emosi di atas rata-rata dalam persepsi emosi. Di sisi lain, ukuran sifat kepemimpinan menunjukan bahwa mereka memiliki sifat kepemimpinan yang tinggi di semua lima sifat kepemimpinan utama. KATA KUNCI: Kecerdasan Emosional; Sifat Kepemimpinan; Guru Kepala Sekolah.Â Â About the Authors: Leilani C. Lucero, M.A. is a Head Teacher at the Pasig City Science High School in the Philippines; and Jose M. Ocampo, Jr., Ph.D. is a Lecturer at the PNU (Philippine Normal University) in Manila, the Philippines. For academic interests, the authors are able to be contacted via their e-mails at: leahcruzlucero@yahoo.com and juno_6970@yahoo.comSuggested Citation: Lucero, Leilani C. Jose M. Ocampo, Jr. (2019). â€œEmotional Intelligence and Leadership Trait among Master Teachersâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Volume 4(1), Maret, pp.55-72. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Article Timeline: Accepted (January 15, 2019); Revised (February 9, 2019); and Published (March 30, 2019).